2006
DOI: 10.4028/www.scientific.net/msf.526.31
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Model for the Straightness Deviation in the Cutting Processes of Aluminum Alloys

Abstract: Light alloys are increasingly applied in different industrial sectors, mainly aerospace. Because of this, it is needed to analyze their behavior in the different processing procedures and, specially, machining. On the other hand, up to a few years, cutting fluids were successfully employed in these processes since their coolant and lubricant properties. Notwithstanding, environmental necessities have promoted researches focused on the development of cleaner processes avoiding cutting fluids, in particular, dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Comparing the differences with the analysis of SD(v) the changes are indicative of a steeper slope. Similar considerations have been found in previous works for aluminium alloys [8]. A similar evolution was found in a previous study on the influence of the cutting parameters on the microgeometrical deviations of dry turned Ti based alloys workpieces [4,9].…”
Section: Resultssupporting
confidence: 89%
“…Comparing the differences with the analysis of SD(v) the changes are indicative of a steeper slope. Similar considerations have been found in previous works for aluminium alloys [8]. A similar evolution was found in a previous study on the influence of the cutting parameters on the microgeometrical deviations of dry turned Ti based alloys workpieces [4,9].…”
Section: Resultssupporting
confidence: 89%
“…Notwithstanding, the most studies that can be found in Literature are commonly focused on the analysis of dimensional parameters, mainly roughness parameters, such as Ra or Rz [2]. So, there is a lack of research works about the study of the surface quality under the point of view of geometrical deviation parameters [3,4].…”
Section: Introductionmentioning
confidence: 99%